2020
DOI: 10.26719/emhj.19.058
|View full text |Cite
|
Sign up to set email alerts
|

Community pharmacists’ perceptions, awareness and practices regarding counterfeit medicines: a cross-sectional survey in Alexandria, Egypt

Abstract: Background: Counterfeit medicines are a threat to public health and the national economy in Egypt. The many community pharmacists in the country could help prevent counterfeit medicines reaching the patient. Information on community pharmacists' perceptions of counterfeit medicines is lacking. Aims: This study assessed the awareness, practices and perceptions of community pharmacists in Alexandria, Egypt with regard to counterfeit medicines. The aim was to identify gaps and inadequacies in pharmacy practice th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 16 publications
2
15
1
Order By: Relevance
“…Whereas in our study 30.6% (95% CI 25.6-35.7%) of the participants could correctly identify counterfeit medications, a similar study conducted in England (n = 320) reported that 62.8% of the participants were aware of the presence of falsified products purchased online and 11.9% had encountered counterfeit items, of whom only 0.9% reported the counterfeit items to the authorities (31,32).…”
Section: Discussioncontrasting
confidence: 80%
“…Whereas in our study 30.6% (95% CI 25.6-35.7%) of the participants could correctly identify counterfeit medications, a similar study conducted in England (n = 320) reported that 62.8% of the participants were aware of the presence of falsified products purchased online and 11.9% had encountered counterfeit items, of whom only 0.9% reported the counterfeit items to the authorities (31,32).…”
Section: Discussioncontrasting
confidence: 80%
“…In this study the most important nding was high experiences of drug counterfeiting. Most pharmacists thought medicine counterfeiting was widespread in Aksum and a similar practice was reported by study conducted in Alexandria, Egypt; as a result, developing countries should pay close attention to the issue of counterfeit medicines (11).…”
Section: Discussionsupporting
confidence: 58%
“…The tool was developed following an extensive review of literature. 4,7,13,[24][25][26] An iterative process involving 3 faculty members with thematic research and teaching experience in this area was used to develop the questionnaire items. A draft version of all the items in the instrument was reviewed independently by each person, and they suggested changes, additions, and deletions.…”
Section: Methodsmentioning
confidence: 99%